Reoperation in Zygomatico-orbital Trauma: A Review of Patients With Suboptimal Outcomes Following Initial Repair. Issue 3 (September 2020) - Taylor, Richard; Kumar, Deepshikha; Ghelani, Jai; Varley, Iain
Introduction: Treatment to restore anatomy, function, and aesthetics after trauma should involve as little surgical insult as possible. As such, repeated procedures may suggest failed initial management. To date, no predictive factors for failure of primary surgery have been identified. Objectives: The aim of this review was to identify factors affecting the requirement for reoperation following treatment of zygomatico-orbital injuries. Study Design and Methods: A retrospective review of patients undergoing surgery for zygomatico-orbital fractures between 2011 and 2019 in a single UK major trauma center was undertaken. All operative notes and imaging were reviewed independently by 2 authors to classify the fracture patterns for both zygomatic and orbital components of the injury. For all cases, the mode of preoperative imaging the grade of operating surgeon, materials used for fixation, and the surgical approaches were recorded. Results: Coding data identified 432 patients who underwent surgery for zygomatico-orbital fractures. In total, 116 cases were treated with closed reduction and 316 with open reduction and internal fixation; 20 cases required reoperation. There were no significant differences identified between cases requiring reoperation and those who did not. Conclusions: A need for repeated surgery is rare. However, this review identified an increased risk of infection of fixation when an intraoral approach was used and highlights the potential benefits that can be achieved by open reduction and internal fixation when more conservative approaches fail to achieve the desired outcome.